Urbanization and non-communicable disease in Southeast Asia: A review of current evidence - Angkurawaranon C. (Elsevier, 2014)
Objective: Non-communicable diseases (NCDs) have been highlighted as a major public health issue in the Southeast (SE) Asian region. One of the major socio-environmental factors that are considered to be associated with such a rise in NCDs is urbanization. Urbanization is associated with behavioural changes such as eating an unhealthy diet, and a decrease in physical activities, which may result in associated obesity. The SE Asian region also has a substantive burden of infectious disease such as HIV and malaria, which may modify associations between urbanization and development of NCDs. Study design: A systematic review was conducted until April 2013. Methods: Using four databases: EMBASE, PubMed, GlobalHealth and DigitalJournal, the systematic review pools existing evidence on urban-rural gradients in NCD prevalence/incidence. Results: The study found that in SE Asia, urban exposure was positively associated with coronary heart disease, diabetes and respiratory diseases in children. Urban exposure was negatively associated with rheumatic heart diseases. The stages of economic development may also modify the association between urbanization and NCDs such as diabetes. Conclusion: There was pronounced heterogeneity between associations. It is recommended that future studies examine the major constituents of NCDs separately and also focus on the interplay between lifestyle and infectious risk factors for NCDs. Prospective studies are needed to understand the diverse causal pathways between urbanization and NCDs in SE Asia.